The effect of non-contingent and accurate performance feedback on pacing and time trial performance in 4-km track cycling - Mauger, A. R.; Jones, A. M.; Williams, C. A. (British Journal of Sports Medicine, 2011)
Objective To determine whether the provision of comparative performance feedback during 4 km track cycling affects completion time.